Bandwidth Knowledge of Results on the Learning of the Saloon Dart Throwing Task. Issue 2 (April 2014) - Coca-Ugrinowitsch, Alessandra Aguilar; Benda, Rodolfo Novellino; Aburachid, Layla Maria; De Andrade, André Gustavo Pereira; Greco, Pablo Juan; Menzel, Hans-Joacmn Karl; Ugrinowitsch, Herbert
The effects of two different bandwidths of information of Knowledge of Results (KR) were investigated. 54 university students participated. The experiment consisted of an acquisition phase with practice of throwing a saloon dart as accurately as possible at a target lying on the floor 2.5 meters away until a specific area of the target was hit three trials in a row. Narrow bandwidth and Wide bandwidth groups received KR when performance was outside the bandwidth. A Control group received KR after every trial. A transfer test was run 10 min. later with 10 more trials and the target 3.0 m away, with no KR. Analyses showed that narrow KR bandwidth was associated with better learning of real world tasks.